The Effectiveness of Positive Affirmations Combination of Face Acupressure and Aromatherapy Against Anxiety in Preoperative Sectio Cesarean Patients At Sentosa Hospital Bogor - Reni Puspita Sari; Vivi Silawati; Putri Azzahroh (Science Midwifery, 2022)
Currently many mothers choose to give birth using the Caesarean section. The problem experienced by pre-SC mothers is anxiety about the condition of the mother and baby. Efforts that can be made to reduce anxiety in pre-SC mothers are by doing positive affirmations with a combination of full-blooded facial and aromatherapy such as lavender and chitrus aromatherapy. The purpose of this research is to find out the effectiveness of positive affirmations of a combination of face acupressure and aromatherapy on the anxiety of preoperative cesarean section patients at Sentosa Hospital Bogor This type of research is a quasi-experimental designpretest and posttest two group design. The research was conducted at Sentosa Hospital, Bogor. Data collection will be carried out on June 15 – July 15, 2022. The population of this study is patients who gave birth by sectio caesarea electively in June – July totaling 46 people with the technique of sampling technique, namely total sampling. Data were analyzed by univariate and bivariate with Wilcoxon and Mann Whitney test. The data was processed using a computer with the SPSS program. Research resultthere is the effectiveness of positive affirmation of the combination of face acupressure and lavender and chitrus aromatherapy on the anxiety of preoperative cesarean section patients (p value 0.000). And there aredifference in patient anxiety precesarean section surgery between face acupressure intervention with lavender and citrus aromatherapy at Sentosa Hospital Bogor(p value 0.000)